Analysis of the Voluntary National Reports in Europe: Switzerland, Finland, Slovenia, and Spain - Calvillo Cisneros, José Miguel (Revista Española de Desarrollo y Cooperación, 2020)
The analysis and evaluation of the actions implemented by the States in the framework of the 2030 Agenda and the Sustainable Development Goals are transcendental for the follow-up of the commitments acquired to achieve sustainable development in our international society. Voluntary National Reports have become a critical component of the 2030 Agenda and the SDGs in each of the States. Only four Europe States have submitted two reports since the beginning of the implementation of the 2030 Agenda.